2020
DOI: 10.1371/journal.pone.0229150
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exoskeletal gait assistance on the recovery motion following tripping

Abstract: Physical assistant robots improve the user's ability to walk. However, they also potentially affect recovery motion following tripping. The assist algorithm should not interfere with the recovery motion, and should enhance the ability of the user to recover after tripping. Thus, in this study, we investigated the recovery motion affected by the assist robot after tripping. We compared the recovery motion with different reaction algorithms. Principal component analysis revealed the effects of the reaction algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Third, this work compared the Stumble Recovery case to both the Weighted and Walk Only cases to show Stumble Recovery improvement; however, note that the Walk Only case results are specific to the type of walking controller used, and as such other walking controllers may have yielded different results. For example, Akiyama et al ( 2020 ) suggested that their walking controller improved healthy users’ stepping responses after tripping compared to stopping assistance after the perturbation; their walking controller only implemented feedforward torques that assisted hip flexion and knee extension in swing phase, as opposed to the trajectory-tracking controller used here. Still, the authors contend that a trajectory-tracking controller is a common form of walking controller for lower-limb exoskeletons to date, so it was reasonable to use it for the Walk Only case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, this work compared the Stumble Recovery case to both the Weighted and Walk Only cases to show Stumble Recovery improvement; however, note that the Walk Only case results are specific to the type of walking controller used, and as such other walking controllers may have yielded different results. For example, Akiyama et al ( 2020 ) suggested that their walking controller improved healthy users’ stepping responses after tripping compared to stopping assistance after the perturbation; their walking controller only implemented feedforward torques that assisted hip flexion and knee extension in swing phase, as opposed to the trajectory-tracking controller used here. Still, the authors contend that a trajectory-tracking controller is a common form of walking controller for lower-limb exoskeletons to date, so it was reasonable to use it for the Walk Only case.…”
Section: Discussionmentioning
confidence: 99%
“…Hip (Monaco et al ( 2017 )) and ankle (Emmens et al ( 2018 ); Bayón et al ( 2022 )) exoskeleton assistance has been shown to improve stability against balance loss during slips and reduce the effort to maintain balance during pushes, respectively. One study analyzed recovery motion following trips while healthy users wore a bilateral exoskeleton with hip and knee actuation, but only the conditions of continuing walking assistance or stopping walking assistance were analyzed (Akiyama et al ( 2020 )) (i.e., no dedicated stumble recovery assistance). Thus no study has considered dedicated stumble recovery assistance in a knee exoskeleton during swing-phase obstacle perturbations (i.e., trip/stumble perturbations).…”
Section: Introductionmentioning
confidence: 99%
“…In this experiment, we examined the characteristics of the first and second recovery steps after perturbation. According to the PCA results in this study, the relationship between the first and second recovery steps is weak whereas it was extracted in the overground experiment [11] as discussed in the subsection below.…”
Section: Reaction Motion Strategiesmentioning
confidence: 98%
“…Wan et al estimated the tripping risk from a gait experiment performed on a walk lane and concluded that fast walking with a large step length and small cadence decreased the tripping risk [10]. Furthermore, it has been reported that the length of the first and second recovery steps varies among trials and individuals, according to overground tripping experiments using an exoskeleton [11]. Therefore, previous studies have identified several key factors for successful recovery from tripping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation